Ураны хүдрийн дээжинд радий, ураны харьцааг тодорхойлох харьцангуй арга - Ж, Сэрээтэр; Н, Ганбаатар; Ш, Гэрбиш (Scientific transaction of the National University of Mongolia. Physics, 2022)
Simple comparative method for determination of radium and uranium ratio was proposed. This method based on the measurements of y-rays intensities with energies 143 7 and 186 (185,7+186.2) keV for uranium standard ores in which the Ra/U equilibrium is known.